Digital Platform Regulation Global Perspectives on Internet Governance - Flew, Terry; Martin, Fiona R. (Palgrave Global Media Policy and Business, 2022)
This Open Access volume provides an in-depth exploration of global policy and governance issues related to digital platform regulation. With an international ensemble of contributors, the volume has at its heard the question: what would actually be involved in digital platform regulation?'. Once a specialised and niche field within internet and digital media studies, internet governance has in recent years moved to the forefront of policy debate. In the wake of scandals such as Cambridge Analytica and the global 'techlash' against digital monopolies, platform studies are undergoing a critical turn, but there is a greater need to connect such analysis to questions of public policy. This volume does just that, through a rich array of chapters concretely exploring the operation and influence of digital platforms and their related policy concerns. A wide variety of digital communication platforms are explored, including social media, content portals, search engines and app stores. An important and timely work, 'Digital Platform Regulation' provides valuable insights into new global platform-orientated policy reforms, supplying an important resource to researchers everywhere seeking to engage with policymakers in the debate about the power of digital platforms and how to address it.